Directed Attention in Gilles de la Tourette Syndrome - Nellie Georgiou; John L. Bradshaw; Jim G. Phillips (Behavioural Neurology)
Gilles de la Tourette syndrome (TS) is a basal ganglia (BG) disorder, associated not only with hyperkinetic movements but also with attentional impairments. This experiment sought to ascertain whether overt direct visual attention would influence tactile attentional performance in TS, via the use of a vibrotactile choice reaction time procedure involving biased probabilities of event occurrence. Participants were required to look (i.e., direct gaze) either at the hand receiving the most (expected) vibrations, or the hand less often stimulated (the unexpected), for both crossed and uncrossed arm postures. Contrary to our predictions, gaze did not influence attentional performance in TS patients. Furthermore, patients were found not to be sensitive to distributions of event probability; that is, they did not demonstrate normal expectancy effects like controls. Attentional deficits in TS (as in Parkinson’s disease, another BG disorder) may pertain more to difficulties in holding rather than in shifting the focus of attention. Moreover, directing attention towards the unexpected locus in the crossed arm posture improved overall performance in both patients and controls, suggesting that increased task demands (e.g., crossed arm posture), and/or unexpected stimulus location, may be alleviated by directed attention. These impairments may stem from dysfunction in the circuits linking the frontal lobes with the BG.